PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI DIKANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDENRENG RAPPANG - Mutmainnah; Jabbar, Abdul; Latif, Adam (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The purpose of this study was to determine how much influence motivation has on employee performance at the Population and Civil Registration Office of Sidenreng Rappang Regency. The population in this study was 960 people. The sample collection technique was purposive sampling. This type of research is Descriptive Quantitative. Data collection techniques used in this study were observation, questionnaires, literature studies. Data analysis techniques used were validation tests, reliability, and hypothesis testing using IBM SPSS and Likert Scale. The results of this study are the results of the questionnaire obtained from the recapitulation of the Information Technology Use variable 81% are in the